Practice-Based Research: Working in Crip Time - May, Heather (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2023)
This essay investigates the negative consequences of higher education’s ableist obsession with individualism, objectivity, and results, positing practice-based research as a powerful crip alternative to traditional academic models. While traditional models of scholarship aim to separate knowledge from the body that created it, practice-based research locates the body as the source of wisdom, a source to be recognized and celebrated. This essay makes legible the messy bodily experience I had during its writing and intertwines it with an explanation of the autoethnographic research process I undertook to better understand my disabled embodied self during a multi-year creative research process. I situate my experience creating "Awaiting Tiresias" within a tradition of disabled scholar-artist-activists who seek to create time and space for themselves within higher ed. Alison Kafer defines this experience in Feminist, Queer, Crip as reimagining “notions of what can and should happen in time” and “bend[ing] the clock to meet disabled bodies and minds” (27). Indeed, crip scholarship prioritizes the health of those who engage in it and the transformations that occur through the research and dissemination process instead of results. This essay argues that through its commitment to challenging assumptions, participating in ongoing and collaborative research methods, and recognizing the central role of the researcher’s body in the research process, practice-based research serves as a crip intervention in ableist scholarship practices.